Strategies for the Treatment of Parkinson’s Disease: Beyond Dopamine - Iarkov, Alexandre; Barreto, George E.; Grizzell, J. Alex; Echeverria, Valentina (Frontiers in Aging Neuroscience, 2020)
Parkinson´s disease (PD) is a neurodegenerative disorder characterized by a progressive loss of dopaminergic neurons and the presence of intracellular -synuclein-positive inclusions. Therapeutic approaches have been directed to reduce the effects of the pathology, b) the restoration of the dopaminergic system, and c) prevent the progression of the pathology by stopping the death of dopaminergic neurons in the midbrain. In here, the fundamental physiological mechanisms involved in PD, the problems involved in developing these therapies and the progress and prospects of each of them are described. In the light of modern views on the nature of PD and expected new forms of early diagnosis, the use of the preventive approach to the treatment of PD appears to be the most effective strategy. However, it will require reliable biomarkers for an early diagnosis at asymptomatic stages of the disease using a personalized and integral treatment.